Pengamatan Atas Daerah Interface Pada Cladding Material Stainless Steel Terhadap Baja Karbon Rendah Secara Metalografi dan Uji Keras - Yohanes Hutahaean; Sahat Mauli Lubis; Charles Manurung; Salomo Simanjuntak; Yetty R Saragi (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2021)
Low carbon steel metal is a type of steel that has poor corrosion resistance. For that it is necessary to protect against corrosion through a coating process. In this case the coating is carried out using solid metal and is known as cladding. In this cladding process using another metal as a coating medium, namely stainless steel, the specimen will be given additional deformation from the outside in the form of pressure and the heating process is carried out above the recrystallization temperature (950oC) then cooled slowly in free air. The heating process of the specimens was carried out with three temperature variations, namely 750oC, 850oC and 950oC with a holding time of 60 minutes, from the research results obtained that the specimens and the highest temperature, 950 oC, had better metal bonds compared to specimens at temperatures of 750 and 850oC with hardness values. average 227.96 VHN.